2021
DOI: 10.1111/ppc.12755
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare workers' anxieties and coping strategies during the COVID‐19 pandemic in Turkey

Abstract: Purpose This study aimed to investigate the anxiety levels of healthcare workers and the coping strategies they used for stress during the COVID‐19 pandemic. Design and Methods This descriptive cross‐sectional study was carried out in April 2020 in Turkey with 444 healthcare workers via three online questionnaires: A participant information form, the State Anxiety Inventory (SAI), and the Ways of Coping Questionnaire. Findings Healthcare work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
2
25
1
Order By: Relevance
“…Other factors may be at play. For example, personality attributes (e.g., resilience, Type D personality) (Labrague and De Los Santos, 2020;Tuman, 2021), coping strategies (Si et al, 2020;Özçevik Subaşi et al, 2021), and impact of the pandemic on family roles have been found to be important contributors to people's well-being during COVID-19 (Cipolotti et al, 2020;Luceño-Moreno et al, 2020). Considering these variables could allow a more comprehensive capture the contributors to people's mental health outcomes in response to the pandemic.…”
Section: Limitationsmentioning
confidence: 99%
“…Other factors may be at play. For example, personality attributes (e.g., resilience, Type D personality) (Labrague and De Los Santos, 2020;Tuman, 2021), coping strategies (Si et al, 2020;Özçevik Subaşi et al, 2021), and impact of the pandemic on family roles have been found to be important contributors to people's well-being during COVID-19 (Cipolotti et al, 2020;Luceño-Moreno et al, 2020). Considering these variables could allow a more comprehensive capture the contributors to people's mental health outcomes in response to the pandemic.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, a longitudinal study conducted in the United States showed that a lower level of positive coping among patients with post myocardial infarction was associated with a higher level of anxiety ( 38 ). Moreover, several studies provided robust evidence for the negative association between positive coping and anxiety among healthcare workers ( 39 , 40 ). Therefore, it could be speculated that positive coping mediated the association between resilience and anxiety among healthcare workers.…”
Section: Introductionmentioning
confidence: 99%
“…23 Some researchers have touched partly on this aspect, although not in detail. 24 The HCWs in our study exercised cautious behavior when they handled any patient, used strict protective measures, minimized outdoor activities, and resorted to meditation and relaxation activities. Some of these strategies were reported during MERS; 10 however, our results show that HCWs embraced these measures more during COVID-19, which reflects the overwhelmingly negative impact of COVID-19 on the HCWs as compared to MERS.…”
Section: Discussionmentioning
confidence: 96%